Confidence in eating disorder knowledge does not predict actual knowledge in collegiate female athletes - Megan E. Rosa-Caldwell; Christopher Todden; Aaron R. Caldwell; Lauren E. Breithaupt (PeerJ, 2018)
Background Eating disorders are serious psychological disorders with long term health impacts. Athletic populations, tend to have higher incidences of eating disorders compared to the general population. Yet there is little known about athletes’ eating disorder knowledge and how it relates to their confidence in their knowledge. Therefore, the purpose of our study was to evaluate collegiate female athletes’ eating disorder (ED) knowledge and confidence in their knowledge. 51 participants were recruited from a National Association of Intercollegiate Athletics (NAIA) university in the mid-west and asked to complete a 30-question exam assessing one’s knowledge of five different categories related to eating disorders. Confidence in the correctness of answers was assessed with a 5-point Likert-scale (1 = very unconfident, 5 = very confident). A one-way ANOVA was used to determine differences between scores on different categories and overall scores. A simple regression analysis was used to determine if confidence or age was predictive in knowledge scores. Results The average score of participants was 69.1%, SD = 10.8% with an average confidence of 3.69/5, SD = 0.33. Athletes scored lowest with regards to Identifying Signs and Symptoms of EDs compared to other sub-scores (p < 0.05). There was no relationship between knowledge and confidence scores. Discussion There is limited ED knowledge among collegiate female athletes. This may be problematic as many athletes appear confident in the correctness of their answers despite these low scores. Coaches should be aware of this lack of knowledge and work with clinical practitioners, such as dieticians, team physicians and athletic trainers to educate and monitor their athletes on eating disorders, specifically signs and symptoms.